Gen therapy and ethical principles - Rodríguez Yunta, Eduardo (Acta Bioethica, 2003)
Gene therapy is a form of genetic manipulation which tries to correct or to diminish the effects caused by genetic diseases. There are great hopes for the development of this type of therapy, specially for somatic genetic diseases that has no cure, but there are many technical difficulties which are not yet solved. It has not yet been shown clinical efficacy and the technique may cause irreversible damages in the organism. On one hand, it is considered necessary to establish regulatory mechanisms to avoid possible abuse and the research protocols must be strictly analyzed by ethical and scientific review committees. On the other hand, at the international level, it is necessary a dialogue between nations in order not to present gene therapy in the market as a successful technique, without mentioning all the technical difficulties. One of the major concerns consists in that the gradual acceptance of this technique and the removal of restrictions may lead to the use of germ gene therapy and genetic enhancement, whose ethical validity is questionable. The use of germ gene therapy carries the risk of introducing genetic damages in posterior generations.